Pediatric Hepatitis A: A Case Report - Sulaiman Yusuf; Fitri Mardia Sari Siregar (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2023)
Background: Hepatitis A is a systemic infection which predominantly inflame the liver due to Hepatitis-A-Virus (HAV) infection. Developing countries have higher prevalence of this disease because of poor sanitation and environment. The transmission of HAV is fecal-oral via contaminated foods or beverages. Case: A 14-year-old boy visited emergency department with yellowish skin on body, nausea, fever, and liver enlargement. He had a bad habit of consuming unhealthy street-foods. Hepatitis A was diagnosed after history taking, physical examination and laboratory testing. Serology test was performed with positive Anti HAV IgM to confirm the disease. Liver enzymes, and bilirubin level were also increased in this patient. Discussion: The transmission of HAV is through fecal-oral via contaminated foods or beverages. This disease can be prevented by having good personal hygiene, avoiding contaminated food, with good access to clean water and environmental sanitation. Habit of consuming street foods is a risk factor of developing HAV infection. The clinical manifestation of HAV infection includes jaundice, nausea, decreased appetite, and vomiting. Conclusion: Diagnosis of hepatitis A requires careful history taking, physical examination and laboratory evaluation. Hepatitis A is a self-limiting disease and currently there is no specific treatment to cure this disease. Supportive treatment, hepato-protector and vitamin supplementation will improve the condition.